2003
DOI: 10.1080/0269905031000089341
|View full text |Cite
|
Sign up to set email alerts
|

Mentally disordered offenders with a history of previous head injury: are they more difficult to discharge?

Abstract: Primary objectives: To identify the incidence of head injury (HI) amongst mentally disordered offenders (MDOs) in UK medium secure units (MSUs), and test the hypothesis that patients with a history of HI are more difficult to discharge than patients without HI. Design, methods and procedures: 113 MDOs being discharged to community settings from five MSUs in England were recruited consecutively between 1/4/99 and 31/12/00. Data on previous HI, offending history, and discharge planning were collected from clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 15 publications
1
34
2
Order By: Relevance
“…Among studies looking at the prevalence of TBI among females offenders (Bogner & Corrigan, 2009; Brewer‐Smyth et al., 2004; Colantonio et al., 2007, 2014; Diamond, Harzke, Magaletta, Cummins, & Frankowski, 2007; Ferguson et al., 2012; Gunter et al., 2009; Hawley & Maden, 2003; Hux et al., 1998; Lewis, Pincus, Feldman, Jackson, & Bard, 1986; Perron & Howard, 2008; Sarapata, Herrmann, Johnson, & Aycock, 1998; Slaughter, Fann, & Ehde, 2003), the rates vary from 9.5% (Perron & Howard, 2008) to 100% (Lewis et al., 1986). A rate of 100% was found in a very small sample of two women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among studies looking at the prevalence of TBI among females offenders (Bogner & Corrigan, 2009; Brewer‐Smyth et al., 2004; Colantonio et al., 2007, 2014; Diamond, Harzke, Magaletta, Cummins, & Frankowski, 2007; Ferguson et al., 2012; Gunter et al., 2009; Hawley & Maden, 2003; Hux et al., 1998; Lewis, Pincus, Feldman, Jackson, & Bard, 1986; Perron & Howard, 2008; Sarapata, Herrmann, Johnson, & Aycock, 1998; Slaughter, Fann, & Ehde, 2003), the rates vary from 9.5% (Perron & Howard, 2008) to 100% (Lewis et al., 1986). A rate of 100% was found in a very small sample of two women.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 21% found in this study confirms previous findings published in Canada and the United States (Bogner & Corrigan, 2009; Brewer‐Smyth et al., 2004; Colantonio et al., 2007, 2014; Diamond et al., 2007; Ferguson et al., 2012; Gunter et al., 2009; Hawley & Maden, 2003; Hux et al., 1998; Lewis et al., 1986; Perron & Howard, 2008; Sarapata et al., 1998; Slaughter et al., 2003). As data about the prevalence of TBI are lacking for Europe, it is hazardous to compare our findings with the prevalence of a history of TBI in the general population in France (Tagliaferri, Compagnone, Korsic, Servadei, & Kraus, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, far less research has examined other cognitive and emotional sequelae of TBI among incarcerated adults, though emotional adjustment problems and mental health issues have been found to be more prevalent among those with TBI (Sarapata, Herrmann, Johnson, Aycock, 1998;Schofield et al, 2006). A number of sequelae beyond an increase in violent behavior have been found among justice-involved individuals with TBI: executive dysfunction (Marsh & Martinovich, 2006); generally poorer cognitive functioning (Sarapata et al, 1998); institutional adjustment problems (Merbitz et al, 1995); and a higher level of risk upon return to the community (Hawley & Maden, 2003).…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…In terms of institutional adjustment, research has shown that offenders with head injury receive significantly more disciplinary infractions while incarcerated (Merbitz et al, 1995;. Offenders with mental disorders and a history of head injury have also been assessed to be a significantly greater risk to themselves and others upon release (Hawley & Maden, 2003).…”
Section: Implications Of Tbi In Offender Populationsmentioning
confidence: 99%